Television franchise in children’s talent show format and gesture in singing performance - Firmino da Silva, Maria Thaís (2019)
Considering the proliferation of negotiations around global televi- sion formats, this research demanded understanding specific relationship be- tween media and music in “The Voice Brasil Kids 2018”. The purpose was to understand how the gestuality evidences gap between the children’s feature of talent show and the meanings implemented in previously determined perfor- mances. This qualitative study (with bibliographic research, content analysis, structural analysis, analysis for the viability of the essence) presents argu- ments about aspects that involve productions in format and is established by the analysis bias that recognizes the gesture as an element of communication with significant impact on the technically mediated performance. Finally, this research pointed out that the gap between the child specificity of the program and the gestures implemented in previously determined performances is sup- ported by the use of gestures with meanings focused on the adult sphere, and the repertoire can also strengthen that perspective.